IKN: Economic Opportunity or Threat? A Comprehensive Public Policy Analysis on the Economic and Social Impacts of Indonesia's Capital City Relocation - Rivandi, Sultan; Pramono, Sidik (Universitas Teuku Umar, 2024)
Indonesia's plan to relocate its capital city from Jakarta to Kalimantan Island, initially proposed by President Joko Widodo in 2019, was formalized in the 2020-2024 National Medium-Term Development Plan (RPJMN). This project, often described as the largest of its kind globally, aims to boost national economic growth and promote economic equity, addressing issues that Jakarta can no longer accommodate. Various economic theories suggest that such relocations have substantial economic impacts, with public policy playing a critical role in determining success. This article analyzes the public policy narrative surrounding the capital city's relocation, particularly from an economic perspective, focusing on its potential opportunities and threats. Using a narrative analysis approach combined with a cross-sectional case study, this research examines the experience of other countries, such as Brazil, as well as statements from Indonesia's Ministry of National Development Planning (Bappenas), which positions Brazil as a reference model. The findings indicate that Indonesia's financial preparedness and the robustness of its public policy framework are pivotal to the success of this relocation. The study explores whether relocating the capital will represent an economic opportunity or a potential threat to Indonesia's future.